2003
DOI: 10.1097/01.mp.0000082394.91761.e5
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Atypia in Nevi: Correlation with Melanoma Risk

Abstract: Nevi with architectural disorder and cytologic atypia of melanocytes (NAD), aka "dysplastic nevi," have varying degrees of histologic abnormalities, which can be considered on a spectrum of grades of atypia. Somewhat controversial and subjective criteria have been developed for grading of NAD into three categories "mild," "moderate," and "severe." Grading involves architectural and cytological features, which often correlate with each other. Architectural criteria were intraepidermal junctional extension beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 35 publications
3
86
0
3
Order By: Relevance
“…Only the superficial dermal expression of CDKN1A differentiated atypical melanocytic nevi-mild from atypical melanocytic nevi-moderate, suggesting that both lesions cannot be reliably distinguished and would favor to group them as low-grade atypical melanocytic nevi. 5,38 Low-grade atypical melanocytic nevus has a revealed association with histologic regression, suggesting that inflammation regression is unlikely to be secondary to neoplastic progression. 45 The histological regression observed in low-grade atypical melanocytic nevi certainly contributes to the atypical clinical picture and is confirmed by a kinetic profile that suggests a regressive lesion; the potential of neoplastic progression in these atypical melanocytic nevi cannot be predicted on histological grounds only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the superficial dermal expression of CDKN1A differentiated atypical melanocytic nevi-mild from atypical melanocytic nevi-moderate, suggesting that both lesions cannot be reliably distinguished and would favor to group them as low-grade atypical melanocytic nevi. 5,38 Low-grade atypical melanocytic nevus has a revealed association with histologic regression, suggesting that inflammation regression is unlikely to be secondary to neoplastic progression. 45 The histological regression observed in low-grade atypical melanocytic nevi certainly contributes to the atypical clinical picture and is confirmed by a kinetic profile that suggests a regressive lesion; the potential of neoplastic progression in these atypical melanocytic nevi cannot be predicted on histological grounds only.…”
Section: Discussionmentioning
confidence: 99%
“…The atypical melanocytic nevus is assumed to represent a malignant melanoma precursor and a marker of increased malignant melanoma risk, 36,37 the risk correlating with the degree of dysplasia. 38,39 The atypical melanocytic nevus grading system is controversial and shows low kappa reproducibility, 40 due to the variable definitions available and the consideration given to moderate dysplasia (either low or high grade). 5,[38][39][40] These definitions tried to reflect the lesion biology, but there are no studies assessing cell kinetics, cell cycle regulators, and cell survival by grade and tumor cell topography.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with severe atypia, the risk of melanoma was almost three-fold greater than for those patients with mild atypia. 7 In the opinion of this author, a pathologist can contribute to the assessment of melanoma risk by identifying histologically dysplastic nevi or nevi with 'dysplastic features'. If these findings are recorded in a pathology report, the clinician should be alerted to assess the risk factors discussed above, and thus to identify individuals whose increased risk for melanoma may warrant lifelong surveillance.…”
Section: Dysplastic Nevimentioning
confidence: 99%
“…Using criteria similar to those discussed above, these observers found that the prevalence of a personal history of melanoma was increased in patients with 'nevi with architectural disorder (NAD)' and various grades of histologic atypia (dysplasia). 7 The grading of atypia involved architectural and cytological features, which were often correlated. Architectural criteria included intraepidermal junctional extension beyond any dermal component, complex distortion of rete ridges, and dermal fibrosis.…”
Section: Dysplastic Nevimentioning
confidence: 99%
See 1 more Smart Citation